2015
DOI: 10.1039/c5ra09405d
|View full text |Cite
|
Sign up to set email alerts
|

Direct synthesis of graphene from adsorbed organic solvent molecules over copper

Abstract: We show the direct synthesis of graphene from adsorbed organic solvent molecules over copper by annealing in hydrogen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 38 publications
(93 reference statements)
3
26
0
Order By: Relevance
“…Furthermore, dynamic phosphorene evolution can be recorded with advanced in situ microscopy and spectroscopy . Another avenue is the chemical equilibrium calculation for reactive radicals (e.g., P 2 concentration) that accounts for the 2D membrane formation.…”
Section: Synthesis Methodsmentioning
confidence: 99%
“…Furthermore, dynamic phosphorene evolution can be recorded with advanced in situ microscopy and spectroscopy . Another avenue is the chemical equilibrium calculation for reactive radicals (e.g., P 2 concentration) that accounts for the 2D membrane formation.…”
Section: Synthesis Methodsmentioning
confidence: 99%
“…[13][14][15][16] Researchers have developed some new binders such as polyrotaxanes, cross-linked carboxymethyl cellulose and citric acid polymer, polyacrylic acid and poly(ethylene glycol) diglycidyl ether with polyethylenimine for LIBs with silicon anode, [17][18][19][20][21][22][23][24][25] lithium-sulfur batteries [26][27][28][29][30][31][32] and other rechargeable batteries. [33][34][35][36][37][38][39] The binders with ionic conductivity are of great interest, due to the fact that they will enhance lithium ion conductivity with high rate capability of LIBs. Recent studies have shown that using lithiated ionomers as binders will provide a path between electroactive materials and electrolytes, which reduces the polarization resistance and increases the ionic conductivity within the electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…It also means that a chemical composition of GO doesn't play a decisive role in shaping the Raman response. Rather, a hybridization of defect sites is responsible for the intensity and line width of the Raman bands 47,48,49,50 . in the sample with 31 at.% of oxygen, the resistance reaches a value beyond our instrument range.…”
Section: Resultsmentioning
confidence: 99%